TAX CONTROL OF TRANSFER PRICES: INSTITUTIONAL ASPECTS OF CONTROL - A. Ardashev (Вестник университета, 2017)
The article examines institutional aspects of transfer pricing control. In the context of institutional economics, integration of tax systems under anti base erosion and profit shifting plan of the Organization for Economic Co-operation and Development shows both its possible positive and negative effects. Such risks shall be recognized during upgrade of exciting tax mechanisms. The author noted that ignoring of similar features of mechanisms of tax control of transfer pricing can turn back decrease in level of tax income and redistribution of such income in other tax jurisdictions.